Should Skepticism Be Discredited? - Ezebuiro, Anthony Udoka; Anichebe, Obiora; Ojimba, Anthony Chimankpam (Conatus - Journal of Philosophy, 2021)
In our day-to-day life and experiences, when one doubts or questions unusually, he is branded a skeptic and consequently resisted. Skeptics, over the years, are seen as people whose basic mood is that of doubt; those who deny absolutely that true knowledge is possible. Although this is not completely true of skepticism, the present work demonstrates, though arguably, that skepticism is more of a philosophical method of inquiry; an epistemological attitude towards knowledge but whose goal is indeed certainty, although it selects a serious doubt concerning all knowledge as the starting point of the inquiry into the possibility of true knowledge. It can rightly be said that the work displays the paradox of skepticism. The word ‘paradox’ originates from a Latin term paradoxum, which has a Greek association paradoxon, or paradoxos, signifying “conflicting with expectation.” Thus, the word paradox signifies a tenet or proposition contrary to received opinions. It is a statement or sentiment that is seemingly contradictory or opposed to common sense and yet, perhaps true in fact. The need for this work is necessitated by the fact that in the present age, it has become no longer the case that the best way to certainty is only by accepting entirely all that one is told, especially when such comes from a sage or a tradition. Obviously, we live in a dispensation where almost every human situation challenges the human rational faculty hence the tendency to change facts and hang-on to lies generates serious fever in every thinking mind. The result of this work therefore is that imperatively, the work demands that whoever wants knowledge should proceed through doubt. The method through which this work arrives at this conclusion is the analytic process of discussion and presentation.